Negation of resultative and progressive periphrases - González Rodríguez, Raquel (Borealis – An International Journal of Hispanic Linguistics, 2015)
This paper focuses on resultative and progressive periphrases in Spanish: <estar ‘to be’ + participle> and <estar ‘to be’ + gerund>, respectively. These periphrases have been associated with several negated constructions. On the one hand, the negative particle no ‘not’ can precede the auxiliary verb (<no estar ‘not to be’ + participle> and <no estar ‘not to be’ + gerund>); on the other hand, we have the structure <estar sin ‘to be without’ + infinitive>. Contrary to what has been suggested in the literature, I will show that these negative constructions have a different interpretation and develop a semantic analysis of them. Furthermore, I will offer new evidence in favor of the existence of negative events.